SELECTED ASPECTS OF HIGHSCHOLL EDUCATION EVALUATION - DOMISCHOVA, Ivona; ZEMANEK, Petr (Trends in education, 2014)
The evaluation and mainly its appropriately set parameters are an important part of appraising the quality of university teaching. The contribution deals with its important aspects, analyses selected evaluative questionnaire used to the evaluation of university teaching abroad, and theoretically analyses selected items from the point of view of their selection.
Keywords: university teaching; evaluation; educator; student; questionnaire.